Proposal for cervical cancer screening in the era of HPV vaccination - Yung-Taek Ouh; Jae Kwan Lee (Korean Society of Obstetrics and Gynecology, 2018)
Eradication of cervical cancer involves the expansion of human papillomavirus (HPV) vaccine coverage and the development of efficient screening guidelines that take vaccination into account. In Korea, the HPV National Immunization Program was launched in 2016 and is expected to shift the prevalence of HPV genotypes in the country, among other effects. The experiences of another countries that implement national immunization programs should be applied to Korea. If HPV vaccines spread nationwide with broader coverage, after a few decades, cervical intraepithelial lesions or invasive cancer should become a rare disease, leading to a predictable decrease in the positive predictive value of cervical screening cytology. HPV testing is the primary screening tool for cervical cancer and has replaced traditional cytology-based guidelines. The current screening strategy in Korea does not differentiate women who have received complete vaccination from those who are unvaccinated. However, in the post-vaccination era, newly revised policies will be needed. We also discuss on how to increase the vaccination rate in adolescence.